HIV-specific CD4 T cell responses to different viral proteins have discordant associations with viral load and clinical outcome - Ranasinghe, Srinika; Flanders, Michael; Cutler, Sam; Soghoian, Damien Z.; Ghebremicahel, Musie; Davis, Isaiah; Lindqvist, Madelene; Pereyra, Florencia; Walker, Bruce D.; Heckerman, David; Streeck, Hendrik (Journal of Virology, 2011)
A successful prophylactic vaccine is characterized by long-lived immunity, which is critically dependent on CD4 T cell-mediated helper signals. Indeed, most licensed vaccines induce antigen-specific CD4 T cell responses, in addition to high affinity antibodies. However, despite the important role of CD4 T cells in vaccine design and natural infection, few studies have characterized HIV-specific CD4 T cells due to their preferential susceptibility to HIV infection. To establish, on the population level, the impact of HIV-specific CD4 T cells on viral control and define the specificity of HIV-specific CD4 T cell peptide targeting, we conducted a comprehensive analysis of these responses to the entire HIV proteome in 93 subjects at different stages of HIV infection. We show that HIV-specific CD4 T cell responses were detectable in 92% of individuals, and the breadth of these responses showed a significant inverse correlation with viral load (p=0.009, R=-0.31). In particular, CD4 T cell responses targeting Gag were robustly associated with lower viremia (p=0.0002, R=-0.45). Importantly, differences in the immunodominance profile of HIV-specific CD4 T cell responses distinguished HIV controllers from progressors. Furthermore, Gag/Env ratios were a potent marker of viral control; with a high frequency and magnitude of Gag responses and low proportion of Env responses associated with effective immune control. At the epitope-level, targeting of three distinct Gag peptides was linked to spontaneous HIV control (Probability=0.60-0.85). Inclusion of these immunogenic proteins and peptides in future HIV vaccines may act as a critical cornerstone for enhancing protective T cell responses.